Perancangan Sistem Informasi Akuntansi Penjualan Berbasis Web Pada Saiioproject Jambi - Johandri Iqbal; Yuventina Laura Hoba (LPPM Politeknik Jambi, 2021)
SAIIOPROJECT Jambi is one of the businesses engaged in the sale of goods and services in the world of photography. Management in the sale of goods and services in this business is still done manually so that the performance in the process of selling goods is still not optimal. In order for optimal management to use a sales information system. This research was conducted in the sales of goods, this information system uses the calculation of COGS (Cost of Goods Sold). The approach method used by the author is data collection, interviews, observation and reference studies and designing a system based on the results of the research conducted. The development of this sales information system uses a waterfall model and the data flow model used is DFD (Data Flow Diagram). Programming language using PHP, Notepad ++ and HTML. This research produces a sales information system that can be implemented in the SAIIOPROJECT Jambi business